2021
DOI: 10.1101/2021.02.27.21251952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence, incidence and risk factors of mental health problems and mental health services use before and 9 months after the COVID-19 outbreak among the general Dutch population. A 3-wave prospective study

Abstract: Objectives. Gain insight in the effects of the COVID-19 pandemic on the prevalence, the incidence and risk factors of mental health problems among the Dutch general population and different age groups in November-December 2020, compared to the prevalence, incidence, and risk factors in the same period in 2018 and 2019. More specifically, the prevalence, incidence and risk factors of anxiety and depression symptoms, sleep problems, fatigue, disabilities due to health problems, use of medicines for sleep problem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…All cohorts reported COVID-19 outcome data collected between March and June 2020. Two large national probability-based cohorts from the United Kingdom 30, 34 and the Netherlands 36, 37, 41 and a cohort of people with a pre-existing medical condition 61 also included data collected between September and November 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All cohorts reported COVID-19 outcome data collected between March and June 2020. Two large national probability-based cohorts from the United Kingdom 30, 34 and the Netherlands 36, 37, 41 and a cohort of people with a pre-existing medical condition 61 also included data collected between September and November 2020.…”
Section: Resultsmentioning
confidence: 99%
“…There were 7 studies 30, 3237 that reported on 5 different general population cohorts, including large national probability-based samples from the United Kingdom (N = 10,918 to 15,376) 30, 34 and the Netherlands (N = 3,983 to 4,064) 36, 37 and 3 convenience samples with 102 to 218 participants per study from Germany, 32 Italy 33 and from multiple countries via an online crowdsourcing platform. 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a longitudinal study in the UK found that racial and ethnic minorities experienced a greater increase in mental distress after the onset of the pandemic as measured by the General Health Questionnaire-12, possibly due in part to lockdowns and physical distancing [ 35 ]. A separate study in the Netherlands found no increase in anxiety or depression at all in the general population after the pandemic began and noted a stable employment situation relative to the U.S. which may play a large role [ 36 ]; the Netherlands’ universal healthcare system and better social safety net (relative to the US) may also explain this difference. With further investigation, these differences may shed some light on the factors contributing to the racial and ethnic disparities in mental health in the US.…”
Section: Discussionmentioning
confidence: 99%